HN1L promotes migration and invasion of breast cancer by up‐regulating the expression of HMGB1. Issue 1 (16th November 2020) - Jiao, Dechuang; Zhang, Jingyang; Chen, Ping; Guo, Xuhui; Qiao, Jianghua; Zhu, Jiujun; Wang, Lina; Lu, Zhenduo; Liu, Zhenzhen
Abstract: Recent reports showed that haematological and neurological expressed 1‐like (HN1L) gene participated in tumorigenesis and tumour invasion. However, the expression and role of HN1L in breast cancer remain to be investigated. Here, bioinformatics, western blot and immunohistochemistry were used to detect the expression of HN1L in breast cancer. Wound healing, transwell assay, immunofluorescence assay and mass spectrum were used to explore the role and mechanism of HN1L on the migration and invasion of breast cancer, which was confirmed in vivo using a nude mice model. Results showed that HN1L was significantly over‐expressed in breast cancer tissues, which was positively correlated with M metastasis of breast cancer patients. Silencing HN1L significantly inhibited the invasion and metastasis of breast cancer cells in vitro and lung metastasis in nude mice metastasis model of breast cancer. Mechanistically, HN1L interacted with HSPA9 and affected the expression of HMGB1, playing a key role in promoting the invasion and metastasis of breast cancer cell. These results suggested that HN1L was an appealing drug target for breast cancer.